Social class and girlhood experiences in selected Indonesian children’s stories - Delita Sartika; Hidayati Hidayati; Armiwati Armiwati (Pioneer: Journal of Language and Literature, 2025)
This study explores how socio-economic background shapes the representation of girlhood in selected Indonesian children’s literature. Guided by Crenshaw’s intersectionality theory, which views identity as shaped by overlapping social categories, this study applies qualitative textual analysis to two storybooks from the Let’s Read Asia project, Cepat Kering, Bunga Kemboja! and Bukan Halangan. By using the close reading method, the analysis focuses on identifying scenes, expressions, and descriptions that construct different forms of resilience through different class contexts. The findings show that Ratih, a working-class girl, develops resilience and independence through financial hardship and self-sacrifice. On the other hand, Kapisa, the girl from a middle-class family, builds resilience through care, guidance, and access to information. These contrasting pathways demonstrate that social class strongly shapes the meaning of resilience and determines whether it is formed by necessity or through privilege. The study concludes that while both stories promote positive images of girls, they also risk normalizing inequality by presenting different class-based realities as equally admirable. These results highlight the importance of examining girlhood experiences at the intersection of gender, class, and age.